Addressing constraints to private financing of urban (climate) infrastructure in developing countries. Issue 3 (2nd September 2019) - White, Roland; Wahba, Sameh
ABSTRACT: Urban infrastructure investment needs in the developing world are immense, particularly when the additional costs associated with lower carbon, more climate-resilient options are considered. These cannot possibly be financed from fiscal sources and ODA flows alone; private financing will need to be accessed. Focusing on the ability of city governments and subnational urban utilities to mobilize private finance, this paper makes two core arguments. First, private investment in municipal infrastructure requires robust institutional, fiscal and regulatory systems that are often absent in developing countries. Establishing such systems often requires policy and institutional reform, much of which lies beyond the competence and control of city governments themselves. Second, while the marginal investment needs related to climate mitigation and adaptation complicate and aggravate the picture, they do not alter the fundamental requirements of private investors. Put simply, municipalities and utilities will need to satisfy the requirements of regular private finance before they can attract green private finance. This paper looks across the main avenues for city governments to mobilize private finance – municipal borrowing, public–private partnerships, and land value capture instruments – and identifies four broad factors that determine the potential size and scope of city leveraging activity. It then offers a new framework to understand where the most pressing constraints to private investment readiness lie and proposes priority measures that local and national governments, together with development partners and other stakeholders, can take to address them.